Peran Live Streaming Dalam Meningkatkan Penjualan Busana Formal Wanita Di Hi.Prima Ngagel Surabaya - Angelina Mahesa Putri; Awin Mulyati (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Digital technology has created new opportunities in marketing, including live streaming, which enables real-time interaction between businesses and consumers. The research employs a descriptive method with a qualitative approach through in-depth interviews with the owner and manager of Hi.Prima. The findings indicate that live streaming effectively expands market reach, enhances consumer engagement, and drives purchasing decisions. Direct interaction during live streaming sessions allows consumers to obtain detailed product information, contributing to a 25-30% increase in sales. Additionally, consistency in execution and creativity in content presentation are critical factors in the success of this strategy. These findings reveal that live streaming is not only a promotional tool but also a strategy to build long-term relationships with customers. This study provides insights for business practitioners to leverage live streaming as an efficient and effective digital marketing strategy in an increasingly competitive market..